2017
DOI: 10.1186/s40463-017-0189-z
|View full text |Cite
|
Sign up to set email alerts
|

Developing a new diagnostic algorithm for human papilloma virus associated oropharyngeal carcinoma: An investigation of HPV DNA assays

Abstract: BackgroundHuman papilloma virus (HPV) has been implicated in the development of a large proportion of oropharyngeal squamous cell carcinoma (OPSCC). Current techniques used to diagnose HPV etiology require histopathologic analysis. We aim to investigate the diagnostic accuracy of a new application non-histopathologic diagnostic tests to help assist diagnosis of HPV-related oropharyngeal tumors.MethodsPatients with OPSCC with nodal metastasis were consecutively recruited from a multidisciplinary cancer clinic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…OPSCC is known to develop cervical nodal metastases in the absence of morphologic features of conventional invasion, and in-situ diagnosis is not used at this anatomical site for practical purposes. The lesions are often small and clinically occult, and patients frequently present with lymph node metastases as compared with HPV negative tumors that commonly present with pain 57 . It is generally accepted that the lack of a continuous basement membrane of the reticular epithelium provides a weak barrier, allowing the HPV-infected cells to develop an invasive tumor front by budding off the basal cell layer with lesser restraint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPSCC is known to develop cervical nodal metastases in the absence of morphologic features of conventional invasion, and in-situ diagnosis is not used at this anatomical site for practical purposes. The lesions are often small and clinically occult, and patients frequently present with lymph node metastases as compared with HPV negative tumors that commonly present with pain 57 . It is generally accepted that the lack of a continuous basement membrane of the reticular epithelium provides a weak barrier, allowing the HPV-infected cells to develop an invasive tumor front by budding off the basal cell layer with lesser restraint.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions are often small and clinically occult, and patients frequently present with lymph node metastases compared with HPV-negative tumors that commonly present with pain. 58 It is generally accepted that the lack of a continuous basement membrane of the reticular epithelium provides a weak barrier, allowing the HPV-infected cells to develop an invasive tumor front by budding off the basal cell layer with lesser restraint. In this study, MOKE6E7 cells showed no organized basement membrane in vivo , but they still formed epithelial lesions confluent with the keratinocytes around the main lumens, likened to the precursor lesions in the conventional SCC.…”
Section: Discussionmentioning
confidence: 99%
“…These statistics were much lower than their fine needle aspirate counterparts. Similar analysis was also done by the same group to evaluate Hologic's Cervista HR and Cervista HPV Genotype (detects specific DNA sequences and targets HPV E6/E7 oncogenes, Marlborough, MA) 104 . Oropharyngeal swabs from 37 patients resulted in a sensitivity of 100% for both tests, with specificities of 33% and 14%, respectively.…”
Section: Salivary Biomarkers Of Hpv‐induced Opsccmentioning
confidence: 95%
“…Similar analysis was also done by the same group to evaluate Hologic's Cervista HR and Cervista HPV Genotype (detects specific DNA sequences and targets HPV E6/E7 oncogenes, Marlborough, MA). 104 Oropharyngeal swabs from 37 patients resulted in a sensitivity of 100% for both tests, with specificities of 33% and 14%, respectively. A similar group recently assessed Atila BioSystems' Ampfire HPV assay (isothermal PCR identification of "various regions in the viral genome including E6/E7," Mountain View, CA); oropharyngeal swabs and saliva resulted in a reported sensitivity of 40.3% and a specificity of 93.3% among 77 tumors.…”
Section: Commercialized Productsmentioning
confidence: 97%
“…Somatic mutations are tested for in a variety of heterogeneous cell sample types, including solid tumors, liquid biopsy, mammalian cell culture, stool, urine, saliva, cerebrospinal fluids, lung lavage, gastric, and tissue and/or organ transplants. [1][2][3][4][5][6][7][8][9] Further, the genetic variants could be single nucleotide polymorphism, multiple mutations, deletion, addition of nucleotides, epigenetic changes (e.g. Methylation), gene expression, splice variants and copy number variations of all the above genetic variants.…”
Section: Introductionmentioning
confidence: 99%